2009
DOI: 10.1021/jz900131x
|View full text |Cite
|
Sign up to set email alerts
|

UV-Irradiation-Enhanced Ferromagnetism in BaTiO3

Abstract: Defect-induced ferromagnetism in nanoparticles has recently attracted extensive attention. We report here that (111) twinned BaTiO3 crystallites synthesized through a modified hydrothermal method can exhibit ferromagnetic properties. The unexpected ferromagnetism is verified to originate from the point defects. We also find that UV irradiation can significantly enhance the ferromagnetism through creating more lattice defects. The photochromic effect is also observed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Recently, Qin et al [21] improved the magnetic properties of semiconductors and found that UV irradiation could significantly enhance the magnetism of the (111) twinned BaTiO 3 crystallites. They demonstrated that magnetism might originate from the increase in oxygen vacancies and Ti 3+ cations formed by capturing an excited electron from Ti 4+ under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Qin et al [21] improved the magnetic properties of semiconductors and found that UV irradiation could significantly enhance the magnetism of the (111) twinned BaTiO 3 crystallites. They demonstrated that magnetism might originate from the increase in oxygen vacancies and Ti 3+ cations formed by capturing an excited electron from Ti 4+ under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetism in these NP has been suggested to be intrinsic and originates from cation or anion vacancies at the surfaces of the NP. Very recently, it was reported from both experiments and first‐principles calculations that typical ferroelectric materials such as BaTiO 3 (BTO) and PbTiO 3 (PTO) become multiferroic when they are prepared at the nanoscale 1–8. So, nanocrystalline BTO offers a room‐temperature magnetic hysteresis as well as temperature‐dependent dielectric constant and a polarization.…”
mentioning
confidence: 99%
“…It is observed experimentally that the multiferroic nature emerges in an intermediate size range of nanocrystalline BTO. Whereas the ferromagnetism is arising from the oxygen vacancies or point defects at the surface of the NP the ferroelectricity is originated from the core of the material 1–3.…”
mentioning
confidence: 99%
“…One is superexchange interaction withinCFO nanoparticles and another isexchange interaction atinterface of BTO and CFO phases. Thus thin layer of 17.5 nm of BTO in CFO@BTO sample favored the magnetization due to surface exchange interaction at the interface [21][22].However, surface spin canting occur due to thin layer of CFO nanoparticles in BTO@CFO nanocomposite that reduced magnetization. respectively.…”
Section: 2microscopic Analysismentioning
confidence: 97%